Shock Wave Attenuation Characteristics of Aluminum Foam Sandwich Panels Subjected to Blast Loading - Jinglin Xu; Jianqing Liu; Wenbin Gu; Xin Liu; Tao Cao (Shock and Vibration)
Comparative experiments were conducted with two different structures to study the mechanism of aluminum foam sandwich attenuating blast shock wave. The sandwich structure is composed of “steel–aluminum foam–steel,” and the mild steel structure is composed of “steel–steel.” In the experiment, the polyvinylidene fluoride transducers were used to directly test the load of stress wave between different interfaces of sandwich and mild steel structures. The strain of back sheet was simultaneously measured using high-precision strain gauge. The accuracy of the test results was verified by Henrych’s formula. Experimental results show that the wave attenuation rate on the mild steel structure is only 11.3%, whereas the wave attenuation rate on the sandwich structure can exceed 90%. The interface effect is clearly a more crucial factor in the wave attenuation. The peak value of back sheet strain in the mild steel structure is much higher than the sandwich structure. The apparent overall “X” crushing band is produced in the aluminum foam core, and scanning electron microscope (SEM) observation clearly shows the collapse of the cell wall. Experiments on the sandwich structure with different aluminum foam densities indicate that increasing the relative density results in increased attenuation capability of the aluminum foam and decreased attenuation capability of the sandwich structure. Experiments on the sandwich structure with different aluminum foam thickness indicate that increasing the thickness results in increased attenuation capability of the aluminum foam and the sandwich structure.